Role of magnetic field and surface corrugation on natural convection in a nanofluid filled 3D trapezoidal cavity - Sehmefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2018)
In this study, the role of magnetic field and surface corrugation on the natural convective transfer characteristics in a three dimensional, CuO-water nanofluid filled trapezoidal cavity was numerically investigated with finite element method. Influence of various pertinent parameters such as Rayleigh number (between 10(4) and 10(6)), Hartmann number (between 0 and 40), number (between 0 and 16) and height (between 0 and 0.5H) of triangular wave form and solid nanoparticle volume fraction (between 0 and 0.04) on the fluid flow and thermal characteristics were analyzed. It was observed that when corrugation height and number of corrugation waves enhance, local and average heat transfer reduce. The use of CuO nanoparticles is advantageous when heat transfer is effective and for the configurations without magnetic field. 26.86% increase in the average Nusselt number is obtained when magnetic field is imposed at Hartmann number of 30 whereas 40.72% of increment in the average heat transfer is attained in the absence of magnetic field when 4% of CuO nanoparticles are added to the water. A mathematical model based on proper orthogonal decomposition and polynomial interpolation among modal coefficients is developed that could be used to reconstruct the whole flow and thermal field and perform thermal predictions for the 3D corrugated cavity.
Keywords: Nanofluid; 3D cavity; Finite element method; Corrugation; POD